The Pandemic Origins of Child Baptism - Arduini, Francesco (The Biblical archaeology review, 2021)
Pandemics can influence and radically alter habits and practices of entire populations. Billions of people have personally tested this phenomenon during the current Coronavirus Disease 2019 (COVID-19) crisis. History knows numerous signs of behavioral practice changes that can be attributed to pandemics, such as the bubonic plague that devastated medieval Europe in the mid-14th […]